Finding Neymar: The Role of Colour in the Detection and Discrimination of Football Kits. (July 2021) - Burnell, Liam; Thompson, Peter
Association Football (hereafter football) is a fast-moving sport in which rapid decisions need to be made; where are other players, are they on my team? Two experiments investigated how kit variations affect the search of teammates. Experiment 1 confirmed that discriminability is slower when playing in crossed kits (e.g., red shirts-blue shorts vs. blue shirts-red shorts), versus uniform kits (e.g., all red vs. all blue). Experiment 2 found that there is significant confusion when both teams wear the same-coloured shorts. Based on these findings, we suggest changes to the Laws of the game concerning kit colours.